Simulation and Evaluation of Soliton Signal Effects In Fiber Optics - Kadhim, Ahmed (Iraqi Journal of Science, 2024)
A soliton is a solitary wave whose amplitude, shape, and velocity are conserved after a collision with another soliton. Solitons, in general, manifest themselves in a large variety of wave/particle systems in nature: practically in any system that possesses both dispersion (in time or space) and nonlinearity. Solitons have been identified in optics, plasmas, fluids, condensed matter, particle physics, and astrophysics. Yet over the past decade, the forefront of soliton research has shifted to neuroscience. The Soliton model in optical fiber is a recently developed model that attempts to explain how signals are propagated within optical fiber without dispersion. In this research, it proposes that the signals travel along the Single Mode Optical Fiber in the form of certain kinds of sound (or density) pulses known as solitons. The three pulses are generated by the Korteweg-deVries equation with Matlab Program. The results of simulation represent the behaviors of the soliton signal in Fiber Optics. Computer simulation results demonstrated that the soliton signal can be successfully used to reduce the dispersion and attenuation effects and travel for a far distance along an optical fiber compared to Gaussian Signal.